Clinical Characteristics and Adverse Events in Acute Coronary Syndrome Patients with a History of Peripheral Arterial Disease - Kang,Yun-Peng (2019)
Abstract Background: In clinical observation, patients with acute coronary syndrome complicated with peripheral artery disease have poor prognosis, so the relationship between the diseases and clinical characteristics need to be further explored. Objective: This study aims to investigate clinical characteristics and independent risk factors for in-hospital adverse events in acute coronary syndrome patients with a history of peripheral arterial disease (PAD). Methods: A total of 5,682 patients with acute coronary syndrome were included into this study. These patients were divided into two groups according to the presence or absence of a history of PAD: PAD group (n = 188), and non-PAD (control) group (n = 5,494). Then, the clinical characteristics and incidence of in-hospital adverse events were analyzed; p < 0.05 was considered statistically significant. Results: The age of PAD patients was higher than that in the control group (65.5 ± 10.3 years vs. 58.6 ± 11 years, p < 0.001), and the proportion of PAD patients with diabetes history and stroke history was higher than that in the control group (73 [39%] vs. 1472 [26.8%], p = 0.018; 36 [19.3%] vs. 396 [7.2%], p < 0.001). The multivariate logistic regression analysis between groups based on in-hospital adverse events revealed that a history of PAD (OR = 1.791, p = 0.01), a history of diabetes (OR = 1.223, p = 0.001), and age of > 65 years old (OR = 4.670, p < 0.001) were independent risk factors for in-hospital adverse events. Conclusion: A history of PAD, advanced age, and a history of diabetes are independent risk factors for in-hospital adverse events in patients with acute coronary syndrome.